2020
DOI: 10.1111/zph.12749
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance of pathogens from ticks collected in New York State suburban parks and schoolyards

Abstract: Schoolyards and suburban parks are two environments where active tick surveillance may inform local management approaches. Even in a state such as New York with a robust active tick surveillance programme operated by the state Department of Health, these settings are not routinely covered. The goal of this study was to highlight the importance of active surveillance for tick‐borne pathogens by describing their prevalence in ticks collected from schoolyards and suburban parks and to guide the use of integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Several studies have identified a positive association between DIN and human incidence [39][40][41][42], although the strength of this association varies spatially [43]. Recreational areas have been identified as high risk environments for exposure to infected ticks [44][45][46][47][48], particularly at woodland-lawn ecotones where tick densities are often the greatest [44,49]. In suburban residential yards, frequently cited risk factors for the acarological hazard include proximity to woodland, lack of fencing, log and brush piles in the yard, bird-feeders and pet ownership [42,44,[50][51][52], all of which may enhance the number of hosts and tick off-host survival.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified a positive association between DIN and human incidence [39][40][41][42], although the strength of this association varies spatially [43]. Recreational areas have been identified as high risk environments for exposure to infected ticks [44][45][46][47][48], particularly at woodland-lawn ecotones where tick densities are often the greatest [44,49]. In suburban residential yards, frequently cited risk factors for the acarological hazard include proximity to woodland, lack of fencing, log and brush piles in the yard, bird-feeders and pet ownership [42,44,[50][51][52], all of which may enhance the number of hosts and tick off-host survival.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate characterization of the microbial communities that are associated with ticks is essential to understanding both the ticks and the diseases they transmit [ 1 , 2 , 3 ]. The most diverse and well-studied components of tick microbiomes are the bacteria [ 4 ], with different bacteria often interacting by interspecific and strain-level competitive displacement [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…POWV carrying ticks and human POWV infections have increased in the Northeastern (N.E.) U.S. (22,35,36) .…”
Section: Discussionmentioning
confidence: 99%